PENGARUH TEKNOLOGI TERHADAP PERKEMBANGAN PASAR VALUTA ASING - Istianatul Ulya; Sadzadia Qothrunnada; Sarpini (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
Technological advances have significantly affected various economic sectors, including the foreign exchange (forex) market. This study aims to analyze the impact of technological developments on the dynamics and efficiency of the foreign exchange market by using descriptive qualitative methods. The results of the analysis show that the application of technologies such as algorithmic trading, blockchain, artificial intelligence (AI), and mobile device-based trading applications have improved accessibility, transaction efficiency, as well as risk management capabilities in forex trading. Moreover, technology has also enabled market participants in emerging economies to participate more inclusively. However, the digitalization of forex trading also presents challenges, including increased market volatility, digital asset risk and cyber threats. The study identifies strategic measures such as diversification of foreign exchange reserves, strengthening financial regulations, and the use of derivative instruments as efforts to manage risks and maintain market stability. With continued optimization of technology, the foreign exchange market can serve as a more stable and efficient economic instrument in supporting international trade activities.